Persepsi Kepala KUA Diwek Jombang Terhadap Penghapusan Batasan Usia Wali Nikah Dalam PMA Nomor 20 Tahun 2019 : Opiniom Of The Head Of KUA Diwek Jombang On The Elimination Of The Age Limit For Marriage Guardians In PMA Number 20 Of 2019 - al khusni, muhammad fatih; Ubaydi Hasbillah, Ahmad (Institut Agama Islam Negeri Fattahul Muluk Papua, 2024)
In PMA Number 11 of 2007 concerning Marriage Registration, it is explained in Article 19 that the requirement for puberty is at least 19 years of age. Meanwhile, in PMA Number 20 of 2019 concerning Marriage Registration, the requirements for marriage guardians as stated in Article 12 paragraph only include puberty without providing information about being at least 19 years old. In this case, the author is interested in researching the opinion of the Head of KUA Diwek Jombang regarding the elimination of the age limit of at least 19 years in PMA Number 20 of 2019 concerning Marriage Registration. The research method uses empirical law, which uses a normative approach and an empirical juridical approach and is analyzed using qualitative and descriptive methods. Observation, interviews and library data are data collection techniques. The results of this research state that the Head of KUA Kec. Diwek District. Jombang, agrees more with the age limit clause, that simply relying on the recognition of ihtilam (wet dreams) as a standard of puberty is not enough, because the fertility level of children today affects their growth, so they show signs of puberty more quickly such as dreams. wet. As a result, it is difficult to determine the exact age when a child experiences a wet dream. To overcome this problem, according to the Head of KUA Diwek Jombang, an age limit is needed to provide legal certainty regarding a child's legal ability to act. Head of District KUA. Diwek District. Jombang is more likely to disagree with the removal of the age limit for puberty, namely 19 years, as a requirement for marriage guardians, even though its implementation follows PMA No. 20 of 2019 concerning marriage registration, because there are inconsistencies in the concept of maturity between PMA No. 20 of 2019 which does not provide a clause limiting the age of puberty along with other regulations.